A meta‐analysis of neurodevelopmental outcomes at 4–10 years in children born at 22–25 weeks gestation. (18th January 2019) - Ding, Sharon; Lemyre, Brigitte; Daboval, Thierry; Barrowman, Nick; Moore, Gregory P.
Abstract: Aim: To update our meta‐analysis on neurodevelopmental disability rates in children born at 22–25 weeks gestation. The main outcome measure was rates of neurodevelopmental disability in survivors at age 4–10 years. Methods: We used a peer‐reviewed electronic and grey search to identify articles. Two authors independently reviewed cohorts published after May 2012 with: born ≥1995 in a developed nation; assessed at 4–10 years; prospective; >65% follow‐up; definitions for neurodevelopmental disability as per the EPICure cohort; results reported by gestation. We contacted authors for clarification. Random effects meta‐analysis was used to estimate pooled proportions of neurodevelopmental disability. Within each study, the absolute change in proportions with each week was estimated and then pooled. Results: We reviewed 3980 records; 21 articles were assessed and six were included. With the previous 9 cohorts, the meta‐analysis now contains 15. Rates of moderate‐to‐severe neurodevelopmental disability were as follows: 42% (95% CI 23, 64%; I 2 0%) at 22; 41% (95% CI 31, 52%; I 2 20%) at 23; 32% (95% CI 25, 39%; I 2 45%) at 24; 23% (95% CI 18, 29%; I 2 60%) at 25 weeks. The analysis shows a significant decrease in risk of moderate‐to‐severe neurodevelopmental disability between each week (8.1% (95% CI −11.8, −4.5%); I 2 0%; p < 0.001). Conclusion: Physicians can use this high‐quality data to support parents during decision‐making.